How Big Is the Media Multiplier? Evidence from Dyadic News Data - Timothy Besley; Thiemo Fetzer; Hannes Mueller (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper estimates the size of the media multiplier, a model-based measure of how far media coverage magnifies the economic response to shocks. We combine monthly aggregated and anonymized credit card activity data from 114 card issuing countries in 5 destination countries with a large corpus of news coverage in issuing countries reporting on violent events in the destinations. To define and quantify the media multiplier we estimate a model in which latent beliefs, shaped by either events or news coverage, drive card activity. According to the model, media coverage can more than triple the economic impact of an event. We show that within our sample, media reporting more than doubled the effect of events in Tunisia and speculate about the role of the media in driving international travel patterns. This concept can easily be generalized to other contexts and settings pending suitable data.
Keywords: O10; F50; D80; F10; L80; 330; media; economic behaviour; news shocks